THE EFFECTIVENESS OF USING TWITTER AS AN EDUCATIONAL TOOL IN DISTANCE EDUCATION (Proceedings of the International Conference on Education, 2023)
The use of social networks in formal and informal learning has led to innovative ways of seeking knowledge over the last decade. Students primarily use social networks for socialisation and entertainment. This study explores how to incorporate Twitter as a social platform to enhance the communication of undergraduate students in the media classroom in the United Arab Emirates and to explain the effect of incorporating Twitter on the learning process and its challenges. The study adopted a convergent parallel mixed method design to collect qualitative and quantitative data from students and teachers by using both open and closed-ended surveys. Quantitive data was analysed descriptively using the mean and the standard deviation. The results revealed that the consistent integration of Twitter in the classroom as an interactive tool for successfully sharing assignments effectively enhances the learning process and communication regardless of the limited number of characters offered by this platform. However, it isn't easy to guarantee the merits of the content. Further studies are needed to develop successful techniques for using Twitter as a pedagogical resource to improve students' demonstrative knowledge of social networking sites.
Keywords: Interface design; Technology acceptance; assessment tool; Digital Media